Joint modeling of forced vital capacity measures with time to onset of polycythemia among chronic obstructive pulmonary outpatients follows‐up: A case of University of Gondar Referral Hospital - Yoseph Kassa; Dessie Melese; Anteneh Asmare; Gashu Workneh (Health Science Reports, 2023)
Abstract Background and Aims Chronic obstructive pulmonary disease (COPD) causes airflow obstruction and respiratory problems. Thus, the main objective of this study was to determine the risk factors for the progression of COPD using longitudinally measured forced vital capacity with time to onset of polycythemia outpatients follow‐up. Methods A retrospective study design was used to gather the related data on longitudinal change of forced vital capacity and time to onset of polycythemia from the medical charts. The joint model consists of a longitudinal submodel for the change of forced vital capacity and a survival submodel for the time to onset of polycythemia of chronic obstructive pulmonary patients. Results From the total of 266 patient's estimated value of forced vital capacity of chronic obstructive pulmonary patients was 74.45 years with a standard deviation of 8.59. The estimated value of the association parameter was −0.006, which indicates that the lower value for a forced vital capacity measure was associated with the higher risk of polycythemia and vice versa “Based on the joint model analysis found that the predictor smoking, comorbidities, marital status, weight, and HIV” jointly affected the two responses, which are change of forced vital capacity and time to onset of polycythemia among chronic obstructive pulmonary patients. Conclusion The overall performance of separate and joint models, joint modeling of longitudinal measures with the time‐to‐event outcome was the best model due to smaller standard errors and statistical significance of both the association parameters.